Neurospora proteome 2000 - Patricia L Dolan; Donald O Natvig; Mary Anne Nelson (Fungal Genetics Reports, 2000)
The filamentous fungus, Neurospora crassa, has an eminent history as a central organism in the elucidation of the tenets of classical and biochemical genetics. Of particular significance are the experiments of George Beadle and Edward Tatum in the 1940s with N. crassa that led to the "one gene-one enzyme" hypothesis (Beadle and Tatum 1941 Proc. Natl. Acad. Sci. USA 27:499 506). In six decades, over 1,000 genes have been mapped and characterized (Perkins, Radford and Sachs 2000 The Neurospora Compendium: Chromosomal Loci. Academic Press; Perkins 2000 Fungal Genet. Newsl., this volume), but that leaves perhaps 10,000 or more genes not yet identified by classical genetics. High-throughput, automated partial sequencing of cDNA libraries to generate expressed sequence tags (ESTs) allows for the rapid identification and characterization of preferentially expressed genes in different tissues, as well as the discovery of novel genes (Adams et al. 1991 Science252:1651-1656; Okubo et al. 1992 Nature Genet. 1:173-179).